The rim of heaven - Howard, Tom, 1937- (Melbourne : Australian Large Print, 1990)
Sergeant Tom Howard is sent to northern New South Wales to investigate a bizarre set of murders. The victims, managers of nearby youth hostels, are all employed by a mysterious society, the Bruning Brotherhood.
Keywords: Talking books